Understanding American Historical Change through Cultural Traditions Physical Environment Literature: A Comparative Reflection in Global Community - Imelda S. Lolowang (Journal of English Language Teaching, Literature and Culture, 2024)
This article embarks on a comprehensive exploration of the intricate interplay between cultural traditions the physical landscape and the realm of poetry or literature particularly in their capacity as architects of public myths within societal consciousness It endeavors to serve as a nuanced comparative reflection offering valuable insights to English language and literature students Leveraging the rich historical and cultural tapestry of America it seeks to illuminate the multifaceted contexts underlying language and literature studies amidst the dynamic trends and formidable challenges of contemporary global society where both tangible and virtual boundaries are increasingly contested Rooted in an understanding spanning from the seventeenth century to the twentieth century the author meticulously selects a myriad of historical records and literary masterpieces each implicitly or explicitly portraying diverse facets of environmental dynamics and the notion of frontier These meticulously curated depictions and conceptual frameworks from various sources constitute the cornerstone of the author s analytical approach elucidating the intricate interconnectedness between American cultural ethos and its surrounding ecological milieu< em>< p>